Reconstruction of paleoenvironment in the Bay of Koper - Ogorelec, Bojan (Annales. Series historia naturalis, 1997)
Geomorphologically, the Bay of Koper (Gulf of Trieste, northern Adriatic) is a wide submerged valley of the Rižana river. Five boreholes drilled in the inner part of the Bay of Koper were used to reconstruct the paleoenvironment of the Bay in the Holocene. These changes are clearly related to the global changes of sea level. The cross-section of the Holocene sediment in the Bay indicates that the early Holocene - late Glacial sediment, dated to about 10-11000 years BP, occurred in the southern part of the Bay when the sea started to enter the Rižana valley...
Keywords: Adriatic Sea; geologija; geology; Gulf of Koper; Gulf of Trieste; Jadransko morje; Koprski zaliv; Tržaški zaliv